2021
DOI: 10.1021/acsami.0c21365
|View full text |Cite
|
Sign up to set email alerts
|

ZnS Ultrathin Interfacial Layers for Optimizing Carrier Management in Sb2S3-based Photovoltaics

Abstract: Antimony chalcogenides represent a family of materials of low toxicity and relative abundance, with a high potential for future sustainable solar energy conversion technology. However, solar cells based on antimony chalcogenides present open-circuit voltage losses that limit their efficiencies. These losses are attributed to several recombination mechanisms, with interfacial recombination being considered as one of the dominant processes. In this work, we exploit atomic layer deposition (ALD) to grow a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…[3,6,20] In terms of ETL, two types of compounds are widely employed, namely, binary oxides, such as TiO 2 , SnO 2 , and sulfides, such as CdS, ZnS. [21][22][23][24][25] The point to emphasize here is that the ETL serves a dual role to Sb 2 (S,Se) 3 device: it not only promotes the separation of charge carriers by forming a heterojunction with the light absorber layer, but also acts as the growth matrix that directly influences the characteristics of Sb 2 (S,Se) 3 film. In the case of oxide ETL, a weak orientating effect on Sb 2 (S,Se) 3 is usually observed because of the large lattice mismatch between them.…”
Section: The Key Role Of Cds In Sb 2 (Sse) 3 Solar Cellsmentioning
confidence: 99%
“…[3,6,20] In terms of ETL, two types of compounds are widely employed, namely, binary oxides, such as TiO 2 , SnO 2 , and sulfides, such as CdS, ZnS. [21][22][23][24][25] The point to emphasize here is that the ETL serves a dual role to Sb 2 (S,Se) 3 device: it not only promotes the separation of charge carriers by forming a heterojunction with the light absorber layer, but also acts as the growth matrix that directly influences the characteristics of Sb 2 (S,Se) 3 film. In the case of oxide ETL, a weak orientating effect on Sb 2 (S,Se) 3 is usually observed because of the large lattice mismatch between them.…”
Section: The Key Role Of Cds In Sb 2 (Sse) 3 Solar Cellsmentioning
confidence: 99%
“…We posit that this τ 2 lifetime is the key in rationalizing the functional operation of PV constructed with these materials. We have recently shown that the efficiency of the completed solar cells fabricated with these materials follows the same trend as the τ 2 lifetime . That is, the efficiency of the cells increases from 0 to 10 cycles of ZnS and then falls off dramatically at 15 cycles.…”
Section: Resultsmentioning
confidence: 75%
“…This series of measurements is instrumental in verifying the photophysical (Figure ) picture we have proposed for this system and is critical to understanding the functional operation of PV cells fabricated with these materials …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Inorganic hole materials show large potential for low-cost and highly efficient Sb 2 S 3 solar cells. [16][17][18][19] Jin et al used NiO x as HTL and obtained PCE of 3.51% for Sb 2 S 3 solar cells. [18] Chen and co-workers reported the material V 2 O 5 HTL for efficient Sb 2 S 3 planar solar cells.…”
Section: Introductionmentioning
confidence: 99%